Visiter Versailles sous l’Empire et la Restauration : musée, palais ou lieu de mémoire ? - Charles-Éloi Vial (Bulletin du Centre de Recherche du Château de Versailles, 2023)
Beyond the platitudes about the oblivion into which Versailles is said to have fallen after 1789, many sources show that the palace continued to attract French and foreign travellers. The views changed from one story to the next, however. Some were looking for vestiges of a lost world or were seeking to nurture their nostalgia, while others on the contrary already saw the palace as a museum of French art or a memorial to the glory of Louis XIV. For a small minority of people, Versailles and its domain, in particular Trianon, remained a place linked to current political events, intended to serve as a residence for the court of the Emperor or that of the restored Bourbons. Published or handwritten autobiographies, private and family correspondence, the papers of the O series of the French national archives and the descriptions published in the press permit a better understanding of those who visited Versailles between 1800 and 1830, in what conditions their visits took place, and also why the place was still frequented, suggesting the early museumification of the palace, in parallel with that taking place at the same time in the palaces actually inhabited by the court.